Behavior of the clinopyroxenes trace elements in spinel-lherzolite xenoliths from Liri (Kapsiki plateau, Cameroon line) - Dagwai, Nguihdama; Pierre, Kamgang; Gbambié Isaac Bertrand, Mbowou; Gilles, Chazot; Ismaïla, Ngounouno (International Journal of Advanced Geosciences, 2020)
Spinel-lherzolite xenoliths trapped within the alkali basalts flow in the Liri region (Kapsiki Plateau) have a protogranular texture and consist of olivine, orthopyroxene, clinopyroxene and spinel crystals. These xenoliths are residues of partial melting of the primitive mantle, with the low titanium content in clinopyroxene crystals (TiO2 < 0.5 wt.%). The clinopyroxene of the spinel-lherzolite xenoliths from Liri, are divided into two distinct groups according to their trace element characteristics. The variations in the rare earths elements make it possible to classify the different clynopyroxenes in two groups: the first group consisting of the samples of Liri (Liri 1, Liri 02, Liri 3, Liri 05 and Liri 5) rich in light rare earths elements (LREEs), with ratios (Ce/Yb)N normalized which vary between 3.00 and 7.78. It is probably a cryptic metasomatism due to the absence of hydrated minerals (such as amphibole) which caused these enrichments. The second group comprises samples of Liri (Liri 01, Liri 2, Liri 04, Liri 4) depleted in light rare earths elements, with the ratio in (Ce/Yb) N < 1.2. This depletion in rare earths elements results from the extraction of the melting liquid.
Keywords: Spinel-Lherzolite Xenoliths; Clinopyroxene; Cryptic Metasomatism; Liri; Cameroon Line.